The art of being dangerous : exploring women and danger through creative expression - Shaw, Jo; Fletcher-Watson, Ben (Leuven University Press, 2021)
The idea that women are dangerous--individually or collectively--runs throughout history and across cultures. Behind this label lies a significant set of questions about the dynamics, conflicts, identities and power relations with which women live today. 'The Art of Being Dangerous' offers many different images of women, some humorous, some challenging, some well-known, some forgotten, but all unique. In a dazzling variety of creative forms, artists and writers of diverse identities explore what it means to be a dangerous woman. With almost 100 evocative images, this collection showcases an array of contemporary art that highlights the staggering breadth of talent among today's female artists. It offers an unparalleled gallery of feminist creativity, ranging from emerging visual artists from the UK to multi-award-winning writers and translators from the Global South.